Impact of COVID-19 on animal health care services, coping practices and associated financial loss to livestock farmers in Karnataka - G, GOVINDARAJ; HM, Swamy; MB, Shanabhoga; GS, Naveenkumar; M, Nagalingam; B, Mahantheshwara; V, Balamurugan; Shome, Bibek; Habibur, Rahman (The Indian Journal of Animal Sciences, 2022)
The COVID-19 pandemic has created a serious impact on the human health and livestock sector. This study assessed the impact of COVID-19 associated lockdowns on animal health services delivery including vaccination, coping practices and financial loss to livestock farmers in Karnataka. A cross-sectional survey among 170 livestock farmers and 24 field veterinarians working in the study jurisdiction were interviewed using a structured schedule questionnaire. A significant decline in the number of hospital cases attended by veterinarians with a major decline in pets (54.9%) followed by goats (35.3%) and sheep (29%) was observed during lockdown. The contact of veterinarian for advices by the farmers through WhatsApp and phone calls increased and Â farmers visit to veterinary hospitals decreased considerably. The applications for welfare schemes that supports livestock farmers were not processed during lockdown. The vaccine administration against Peste des Petits Ruminants (PPR), Enterotoxaemia (ET) and Haemorrhagic Septicaemia (HS) per veterinarian declined in sheep and goats whereas, targeted vaccination against FMD in cattle was achieved. During lockdown, increased mortality of small (75.2%) and large ruminants (14.3%) with a overall increase of 84.8% in the financial loss (112$ per farm) was observed. The COVID-19 and associated lockdown affected the livestock farmers in multiple dimensions. Hence, to cope with the lockdown effects, it is recommended to engage trained personals and Non- Governmental Organisation (NGOâ€™s) associated with animal welfare services to provide uninterrupted veterinary services to the farmers.